The Technology Singularity, Adapting to New Ways of Work - Naik, Nerina Chetty (Digital Repository of Theses, 2026)
Technological advances have transformed human history across successive industrial revolutions, with recent breakthroughs in artificial intelligence accelerating society into a new cognitive age. The possibility of a technological singularity, a point at which technological systems may evolve beyond human capability, could fundamentally reshape work, skills, and organisational structures. In such volatile, uncertain, complex and ambiguous (VUCA) (Johansen & Euchner, 2013) conditions, research is needed to understand the challenges and opportunities this transformation presents for the workforce. History shows that technological revolutions disrupt existing jobs and create new forms of work, often widening divides between those who are able to adapt and those who could get left behind. The rise of AI increases this divide, highlighting the urgent need for new approaches to recruitment, skills development, and workforce planning that prioritise adaptability, resilience, and future readiness. This study investigates how past industrial revolutions have influenced job roles and skill requirements, examines organisational responses to technological disruption, and, in doing so, suggests a strategic framework to guide future workforce planning. Using a qualitative research design, the study incorporates a systematic literature review as well as semi-structured interviews with industry experts, and thematic inductive content analysis following Braun and Clarke’s phases. SWOT analysis and the TOWS framework were used to synthesise strategic insights and strengthen the link between empirical findings and organisational application. The review has highlighted that while technical skills are essential, the long-term workforce readiness actually depends on agility traits that help individuals navigate uncertainty, unlearn outdated practices, and collaborate with emerging technologies. These insights led to the development of the Agility triad, the study’s main conceptual contribution, offering a theoretically grounded and actionable framework for organisations to build sustainable talent strategies amid accelerating technological change. The study concludes with recommendations aligned with the three agility domains, providing organisations with a roadmap to strengthen learning ecosystems, foster psychological and organisational resilience, and enable hybrid human–machine collaboration. Although limited by its qualitative scope and the rapidly evolving technological landscape, the research provides a sturdy foundation for future practical testing and longer-term longitudinal exploration. Overall, the study offers new theoretical insight and practical guidance for workforce planning in an era defined by complexity, disruption, and the emerging technological singularity.